2018
DOI: 10.1136/bmjopen-2018-021510
|View full text |Cite
|
Sign up to set email alerts
|

Does perturbation-based balance training prevent falls among individuals with chronic stroke? A randomised controlled trial

Abstract: ObjectivesNo intervention has been shown to prevent falls poststroke. We aimed to determine if perturbation-based balance training (PBT) can reduce falls in daily life among individuals with chronic stroke.DesignAssessor-blinded randomised controlled trial.SettingTwo academic hospitals in an urban area.InterventionsParticipants were allocated using stratified blocked randomisation to either ‘traditional’ balance training (control) or PBT. PBT focused on improving responses to instability, whereas traditional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 51 publications
6
125
2
1
Order By: Relevance
“…Other studies found similar results between + 3.6 points and 10 points on the ABC scale, over 10 to 30 training sessions using moveable platform perturbations,(46) manual perturbation in a standing position, (19) and an agility exercise program designed to challenge dynamic balance. (14) However, this improvement may not be directly related to perturbation as balance con dence increased by similar amounts between perturbation-and walking-only training.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Other studies found similar results between + 3.6 points and 10 points on the ABC scale, over 10 to 30 training sessions using moveable platform perturbations,(46) manual perturbation in a standing position, (19) and an agility exercise program designed to challenge dynamic balance. (14) However, this improvement may not be directly related to perturbation as balance con dence increased by similar amounts between perturbation-and walking-only training.…”
Section: Discussionmentioning
confidence: 61%
“…Improvement in RNLI scores after perturbation training supports the fact that improvements in balance abilities translated into better participation and mobility in the community. Previous studies that used progressive standing perturbations (19) or low-intensity gait perturbations(20) did not transfer to daily-life mobility. It is possible that the more intense and higher number of gait perturbations used in our study may have had a better effect on mobility and thus on community reintegration.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Mans eld et al [22] suggested that post-stroke rehabilitation strategies for fall prevention should incorporate training of dynamic balancing responses following perturbations that challenge balance by focusing on remediating dysfunction of the more affected limb. Several studies reported that perturbation-based balance training has a positive effect on improvement of reactive dynamic balancing responses following unexpected loss of balance, which might reduce the risk of falling among older adults and clinical populations [14,[23][24][25][26][27].…”
Section: Squarementioning
confidence: 99%